Biology, chance, or history? The predictable reassembly of temperate grassland communities. - Petermann, J; Fergus, A; Roscher, C; Turnbull, L; Weigelt, A; Schmid, B (2010)
Many studies have examined invasion resistance in plant communities, but few have explored the mechanisms of invasion and how subsequent community reassembly affects community functioning. Using natural dispersal and deliberate seed addition into grassland communities with different compositional and richness histories, we show that invaders establish in a nonrandom manner due to negative effects of resident functional groups on invading species from the same functional group. Invaders hence complement communities with originally low richness levels. Consequently, communities converge toward similar levels of species richness, high functional richness, and evenness, but not always maximum productivity. Invasion processes are faster but qualitatively similar when the effect of chance, in the form of dispersal stochasticity, is reduced by seed addition. Thus, dispersal limitation may influence community assembly, but it does not override functionally predictable assembly mechanisms. Some of the most productive communities prior to invasion are unstable in the face of invasion, leading to decreased productivity following invasion. We suggest that invasion into such communities occurs possibly because a pathogen-free niche is available rather than a resource niche. Thus, pathogens in addition to resource niches may be important biological drivers of community assembly.